2014
DOI: 10.1590/s0100-736x2014000100016
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of fifteen microsatellite loci in Brazilian (blue-egg Caipira) chickens

Abstract: The purpose of this study was to investigate the genetic polymorphism of fifteen microsatellites loci in Brazilian (blue-egg Caipira) chickens. Samples were collected from 100 blue eggs of Caipira chickens from rural properties in the city of Dois Lajeados, RS. After DNA extraction, the fragments related to molecular markers LEI0248, LEI0221, LEI0214, LEI0192, LEI0217, LEI0254, LEI0194, LEI0212, MCW0371, ADL0278, LEI0234, MCW0183, MCW0216, MCW0330 and MCW0081 were obtained by polymerase chain reaction (PCR). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
(33 reference statements)
3
5
0
4
Order By: Relevance
“…Os polimorfismos genéticos apresentam relevância em análises das relações genéticas entre subpopulações de uma espécie (Hartl & Clark, 2010). Estudos com galinhas mostram a importância dos microssatélites em análises de parentesco e diversidade genética, e as informações oriundas desses marcadores microssatélites podem auxiliar no planejamento de cruzamentos tecnificados, reduzindo valores expressivos de taxas endogâmicas e perda de alelos no melhoramento dos animais (Qu et al, 2006;Fonteque et al, 2014 Os valores totais médios da heterozigosidade dos plantéis (Ho: 0,674 e He: 0,887), do presente estudo, de galinhas Canela-Preta foram considerados intermediários. Foram considerados níveis altos aqueles ˃ 0,7, e baixos aqueles ˂ 0,5 (Clementino, 2010).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Os polimorfismos genéticos apresentam relevância em análises das relações genéticas entre subpopulações de uma espécie (Hartl & Clark, 2010). Estudos com galinhas mostram a importância dos microssatélites em análises de parentesco e diversidade genética, e as informações oriundas desses marcadores microssatélites podem auxiliar no planejamento de cruzamentos tecnificados, reduzindo valores expressivos de taxas endogâmicas e perda de alelos no melhoramento dos animais (Qu et al, 2006;Fonteque et al, 2014 Os valores totais médios da heterozigosidade dos plantéis (Ho: 0,674 e He: 0,887), do presente estudo, de galinhas Canela-Preta foram considerados intermediários. Foram considerados níveis altos aqueles ˃ 0,7, e baixos aqueles ˂ 0,5 (Clementino, 2010).…”
Section: Resultsunclassified
“…Foram considerados níveis altos aqueles ˃ 0,7, e baixos aqueles ˂ 0,5 (Clementino, 2010). Outras pesquisas com galinhas crioulas mostraram níveis baixos de média de heterozigosidade: Ho=0,491 e He=0,756 em galinhas crioulas brasileiras produtoras de ovos azuis (Fonteque et al, 2014); Ho=0,380 e He=0,475 em frangos nativos de Turquia (Kaya & Yildiz, 2008); e Ho=0,5 e He=0,6 em frangos de raças indígenas (Chatterjee et al, 2015). No entanto, foram encontrados níveis altos de heterozigosidade (Ho=0,785 e He=0,687) em ecótipos de galinhas brasileiras (Clementino et al, 2010).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…The phenotypic performance studies (Khan et al, 2004, Khan et al, 2007, Faruque et al, 2010 suggested that the hilly chickens are comparatively better than other native chickens. Although the genetic characterization study using microsatellite marker of different native chicken's populations are available in the literature (Fonteque et al, 2014, Nedup et al, 2012, Zanetti et al, 2010 however, these literatures lack information on hilly chickens of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%